Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1365-2559.2011.04086.x
|View full text |Cite
|
Sign up to set email alerts
|

Intramucosal variant of nasal natural killer (NK)/T cell lymphoma has a better survival than does invasive variant: implication on loss of E26 transformation‐specific sequence 1 (ETS‐1) and T‐box expressed in T cells (T‐bet) with invasion

Abstract: NNKTCL is classically an aggressive lymphoma, but the intramucosal variant is less aggressive. Loss of ETS-1 or T-bet correlated weakly with invasion, a finding that requires further confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Recently, there are improvements in the validated benefit of L-asparaginase-based regimens combined with radiotherapy in patients with early stage ENKTL [22][23][24] . However, there is still quite a large proportion of patients with stage IE/IIE ENKTL with unappealing outcomes due to disease recurrence or metastasis [3][4][5] . Therefore, intensive systemic therapy is necessary to prolong survival and improve prognosis in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there are improvements in the validated benefit of L-asparaginase-based regimens combined with radiotherapy in patients with early stage ENKTL [22][23][24] . However, there is still quite a large proportion of patients with stage IE/IIE ENKTL with unappealing outcomes due to disease recurrence or metastasis [3][4][5] . Therefore, intensive systemic therapy is necessary to prolong survival and improve prognosis in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Its main histologic changes are shown as obvious vascular destruction, tissue necrosis, and cytotoxic phenotype and closely associated with Epstein-Barr virus infection [2] . Although most patients with ENKTL were diagnosed with stage IE/IIE, previous studies confirmed that quite a few cases were correlated with unsatisfactory treatment outcomes because of highly aggressive biological behavior, rapid disease progression, and recurrence [3][4][5] . So far, unified treatment strategies have not yet been established for this disease.…”
mentioning
confidence: 99%
“…This intramucosal variant may lack the prototypical angiocentricity and angiodestruction previously considered to be absolute characteristics (1). Although classically an aggressive lymphoma, intramucosal ENKTL appears to be less so (1,7,8). Some reports also suggest that ENKTL with a significant small cell component may portend a more favorable clinical prognosis (2,5).…”
Section: Discussionmentioning
confidence: 99%
“…Their series also confirms the poor prognosis. According to Lin et al [25], intramucosal cases do much better and that there seems to be some association between invasive growth and loss of ETS1.…”
Section: B-cell Lymphomasmentioning
confidence: 98%